Exstraordinary and planar Hall effects in thin permalloy films - Halauchyk, Victoryia I.; Lukashevich, Michail G. (Journal of the Belarusian State University. Physics, 2021)
The Hall resistance hysteresis loops in thin (d = 80 –280 nm) magnetically ordered permalloy films (Ni0.8 Fe0.2) were studied at room temperature at different angles between the film plane and the magnetic field direction (φ = 0 –360°) (extraordinary and ordinary Hall effects), at different angles (θ = 0 – 90°) between the magnetic field direction and the flowing current (planar Hall effect at φ = 0°) in a magnetic field up to B = 1.25 T. The thin films were obtained on sitall dielectric substrate by ion beam sputtering. Sharp peaks of the Hall resistance were observed in the extraordinary and planar Hall effects during the magnetisation reversal of the films due to a change of the magnetisation direction with respect to the sampling current direction. In the extraordinary Hall effect the position and full width at half maximum of a peak is determined by the angle between the magnetic field direction and the film plane. It has been shown that as the direction of the external magnetic field approaches the spontaneous magnetisation direction, both the peak magnetic field position Bp and the full width at half maximum of the peak Δ Bp increase. In the angles range of φ = 0 – 90° Bp and Δ  Bp varies in the magnetic field range from Δ  В ≈ 0.2 to 5.0 mT. A non-monotonic dependence of the planar Hall resistance and its peak position on the angle between the flowing current and the magnetic field direction was detected. It is related to the change of the longitudinal and transverse components the resistance of the magnetically ordered solids by an external magnetic field. The values of the ordinary and extraordinary Hall effects coefficients have been determined: RH0 = 6 ⋅ 10–9 m3/C and RH1 = 3.2 ⋅ 10–8 m3/C, respectively.
Keywords: permalloy; exstraordinary Hall effect; planar Hall effect; substrate; film; magnetic ordering